2022
DOI: 10.1038/s41598-021-04607-8
|View full text |Cite
|
Sign up to set email alerts
|

Effects of transcranial alternating current stimulation over right-DLPFC on vigilance tasks depend on the arousal level

Abstract: Current theoretical accounts on the oscillatory nature of sustained attention predict that entrainment via transcranial alternating current stimulation (tACS) at alpha and theta frequencies on specific areas of the prefrontal cortex could prevent the drops in vigilance across time-on-task. Nonetheless, most previous studies have neglected both the fact that vigilance comprises two dissociable components (i.e., arousal and executive vigilance) and the potential role of differences in arousal levels. We examined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 69 publications
2
14
0
Order By: Relevance
“…The main effect of time-of-day was statistically signi cant, F(1, 38) = 5.61; p = .02; η p 2 = .13, which indicated that, in general, performance at the optimal time produced shorter RTs (319 ms) than at the non-optimal time (341 ms). The difference in performance between the optimal and non-optimal time-ofday according to the different chronotypes is referred to as the synchrony effect and the current results replicate those obtained in other experiments using the same task (11,35,40). Accordingly, the current synchrony effect con rms the appropriate selection of our sample of extreme chronotypes.…”
Section: Experiments 1: Intermediate-type Chronotypesupporting
confidence: 82%
See 1 more Smart Citation
“…The main effect of time-of-day was statistically signi cant, F(1, 38) = 5.61; p = .02; η p 2 = .13, which indicated that, in general, performance at the optimal time produced shorter RTs (319 ms) than at the non-optimal time (341 ms). The difference in performance between the optimal and non-optimal time-ofday according to the different chronotypes is referred to as the synchrony effect and the current results replicate those obtained in other experiments using the same task (11,35,40). Accordingly, the current synchrony effect con rms the appropriate selection of our sample of extreme chronotypes.…”
Section: Experiments 1: Intermediate-type Chronotypesupporting
confidence: 82%
“…To ensure the appropriate selection of our sample of extreme chronotypes, we used the psychomotor vigilance task (PVT). This task has been shown to be very sensitive to circadian-related performance (34) and has been widely used in cognitive research (11,12,35,36). To assess the effects of chronotype and time of testing on automatic processing, we explored facilitatory priming with a short prime-target SOA (100 ms).…”
Section: Introductionmentioning
confidence: 99%
“…Second, tDCS was conducted in the offline mode before cognitive fatigue occurred. Both groups were at a good arousal level and emotional state before tDCS, resulting in no significant enhancement of tDCS in a state-dependent manner (Martínez-Pérez et al, 2022).…”
Section: Discussionmentioning
confidence: 93%
“…This may be related to participants’ basal state. A study showed that transcranial alternating current stimulation (tACS) at alpha frequency improved executive vigilance in the SART only when arousal was low ( Martínez-Pérez et al, 2022 ). In this study, both groups were at a good arousal level and emotional state before tDCS (see Table 1 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation